1989
DOI: 10.1161/01.hyp.14.3.274
|View full text |Cite
|
Sign up to set email alerts
|

Brain angiotensin II and baroreceptor reflex function in spontaneously hypertensive rats.

Abstract: We examined whether the increase in baroreceptor reflex function previously reported in lifetime-captopril-treated spontaneously hypertensive rats (SHR) was due to an inhibition of brain angiotensin II mechanisms. Pregnant and lactating SHR were given oral captopril (100 mg/kg/day). After weaning, pups were maintained on captopril (50 mg/kg/day) until the study (19-21 weeks). Control rats received tap water. One week before study captopril-treated and control SHR were given an intracerebroventricular infusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…The site where Ang II affects the baroreflex could include the baroreceptors 26 -27 and the CNS."' 23 However, we found in the present study that enalapril, which suppresses the RAS, exerted no effect on the baroreceptor activity in WKY rats while trichlormethiazide, which may stimulate or at least does not inhibit the RAS, and enalapril had similar effects on the baroreceptor activity in SHRs. It seems unlikely therefore that the anesthesia affected the baroreceptors through actions on the RAS.…”
contrasting
confidence: 71%
“…The site where Ang II affects the baroreflex could include the baroreceptors 26 -27 and the CNS."' 23 However, we found in the present study that enalapril, which suppresses the RAS, exerted no effect on the baroreceptor activity in WKY rats while trichlormethiazide, which may stimulate or at least does not inhibit the RAS, and enalapril had similar effects on the baroreceptor activity in SHRs. It seems unlikely therefore that the anesthesia affected the baroreceptors through actions on the RAS.…”
contrasting
confidence: 71%
“…These data suggest that ACE inhibitors, more than antirenin immunization, reduce the generation of angiotensin II within the central nervous system, where it specifically depresses cardiac baroreceptor reflex responses to increases, but not to decreases, in blood pressure. 27 - 28 However, it has been recently shown that brain ACE was not consistently decreased by most of the ACE inhibitors. 29 In addition, antirenin immunization also tended to increase the baroreceptor reflex sensitivity.…”
Section: Figure 4 Bar Graphs Showing the Free Urinary Catecholaminesmentioning
confidence: 99%
“…Berecek and colleagues (15)(16)(17)(18)(19)(20)(21) have shown that lifelong treatment of SHR by an angiotensin-converting enzyme inhibitor, captopril, completely blocks the development of hypertension and related cardiovascular derangements in adult animals. Even when treatment is discontinued at age 8 wk, captopril-treated SHR (cap-SHR) indefinitely maintain normal blood pressure and heart rate (15)(16)(17)(18)(19)(20)(21), as well as an absence of the vascular changes and cardiac hypertrophy typically observed in SHR (19).…”
mentioning
confidence: 99%